The Crisscrossing of Time in Spenser’s Amoretti LXXV and Shakespeare’s Sonnet XVIII - Araujo, Laura Ribeiro (Indonesian Journal of English Language Studies (IJELS), 2022)
Time is a prevalent motif in Elizabethan love sonnets, presenting itself not only as natural force to be reckoned, but also as an oppositional element in humanity’s constant search for immortality. Through the analysis of both Edmund Spenser’s Amoretti LXXV and William Shakespeare’s Sonnet XVIII I intend to explore, compare and contrast the representations of Time in their verses as well as the poets’ promises of immortality through their own writings. Drawing from Horace’s Odes and Ovid’s Metamorphoses as referential works in the discussion of Time in poetry, I will highlight how the struggle to survive the natural passage of time and its corrosive effects while having art as medium may have inspired both Spenser and Shakespeare’s efforts into building their own metonymical pieces of art. Through this work I hope to delve further into the motif of Time as a force that opposes the logic of stability and immutability often proposed by an art that promises the immortalization of one’s love interest.